The Impact of Tourism Architecture on Culture and Communities in Tropical Region – on the example of Bali. - Praschan, Rabea (Institute for Research and Community Services Udayana University, 2025)
This paper examines the impact of tourism architecture on local communities and cultural identity in Bali. The rapid growth of tourism has driven significant changes in traditional residential structures, cultural practices, and social dynamics, leading to concerns about the erosion of Bali’s unique heritage. The increasing demand for modern tourist facilities has disrupted the traditional balance between architecture, culture, and community life. Sacred spaces and traditional layouts are being replaced by structures designed to meet the needs of tourism, resulting in the fragmentation of communities and the loss of cultural authenticity. Traditional rituals and practices have been commodified, further weakening the social and spiritual fabric of the island. The findings highlight the critical challenges posed by unregulated tourism development, which threatens both cultural identity and environmental sustainability. Bali’s situation illustrates the broader challenges faced by regions seeking to balance tourism growth with the preservation of cultural and ecological heritage. This work emphasizes the importance of sustainable practices that respect local traditions while addressing the pressures of global tourism. It provides valuable insights for understanding the transformative effects of tourism architecture on culture and community life.